SHORELINE CHANGE THREAT TO COASTAL ZONE: A CASE STUDY OF KARWAR COAST (The Proceedings of The International Conference on Climate Change, 2018)
Shoreline is a triple interface of air, water and land and also the wet and dry boundary between land and sea. It is key geo-indicator of coastal environmental resource threats within the coastal zone. Shoreline change leads to causes for change in natural habitats, infrastructure change in the coastal zone and so on. These changes which rise to serious issues those are related to the coastal zone. The present study is carried out for the Karwar Coast, West Coast of India, using remote sensing and GIS Techniques. LANDSAT-8 remote sensing data which is available from 2013, coupled with GIS techniques used for the shoreline analysis. The acquired image was subjected to layer stacking to remove errors from raw image data using ERDAS IMAGINE 2014 tool and analyzed by ArcGIS 10.3 tool. For extraction of shoreline the High-Water Line (HWL) considered and visual interpretation of satellite imageries has been carried out to segregate the HWL, in addition to this to collect the ground truth data, the shoreline track is carried out using Trimble GPS (Global Positioning System) device. Digital Shoreline Analysis System (DSAS) were used to find rates of change of shoreline such as End Point Rate (EPR), Net Shoreline Movement (NSM). Results were concentrated on EPR as the analysis was carried for every two years from 2013 to 2017 of post- monsoon period to find out erosion and accretion. It is found to be Tagore beach is changed from accretion zone to erosion zone, and Devbagh beach is experiencing erosion. The study finds that the shoreline change is threatening to Karwar coastal zone.
Keywords: Shoreline; HWL; EPR; NSM